Financial Adviser Anxiety, Financial Literacy, and Financial Advice Seeking. Issue 1 (23rd August 2016) - Gerrans, Paul; Hershey, Douglas A.
Abstract : Seeking professional financial advice to assist with financial decision making is an important option for consumers faced with increased responsibility for their own financial circumstances. We explore the role of two potential barriers/enablers to accessing financial advice. First, we explore the role of a variety of financial literacy measures to explain observed financial advice consultation. Second, we introduce a newly developed measure of financial adviser anxiety. We define adviser anxiety as (an existing or prospective clients') concerns involving the prospect of meeting with a financial adviser. The notion of adviser anxiety is inspired by evidence from medical settings that suggest individuals may refrain from seeking advice when objectively, it is in their best interests to do so. This anxiety may be due to embarrassment, worry, or other forms of apprehension associated with the consultation process. A new scale is presented which has strong validity and a demonstrated ability to explain reported future levels of professional advice seeking.